Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan (Studi Kasus Pelanggan Grab-Motor Di Kota Makassar) - Ambo Paerah; reijeng tabara; Syahribulan syahribulan (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
This study aims to determine the effect of service quality on customer satisfaction for Grab Motor Makassar branch. This type of research is a sampling study using a simple linear regression analysis method with a quantitative approach. The research population is all consumers of Makassar City Grab Motors during the month of July, where the exact number cannot be known or is called the infinite population. Thus the research sample is part of the research population that is used as the research subject, with a total sample of 139 respondents obtained by purposive sampling method with incidental technique. The results showed that the service quality variable partially had a positive and significant effect on customer satisfaction. Based on the value of the Adjusted Coefficient of Determination, it shows that all contributions between service quality and customer satisfaction are 54%.